Towards the Neutralization of the Carbon Footprint at the Autonomous University of the State of Mexico - Juan Roberto Calderon Maya; Carlos Eduardo Barrera Diaz; Noe Armando Colin Mercado; Yoselin Montoya Garcia; Francisco Javier Rosas Ferrusca (Journal of Sustainability Perspectives, 2024)
The primary objective of the research was to calculate the carbon footprint resulting from the substantive activities of the Autonomous University of the State of Mexico between the years 2021 and 2022, to propose strategies for carbon footprint neutralization. The scientific and methodological contribution of this research can serve as a model for Mexican universities that wish to measure their carbon footprint. The research encompasses several sections. The first section delineates the issues pertinent to this study, along with the primary objective and specific goals. The subsequent section defines the conceptual framework employed. Regarding the state of the art of this research, it was necessary to identify that it is doing in this regard in other latitudes, which is why an analysis is presented of some of the universities in Europe and Latin America that have added work and effort to carry out studies on their greenhouse gases emissions generated and, in some cases, have achieved quantify their ecological or carbon footprint. The proposed methodology takes up the guidelines of the ISO 14064-1:2019 standard and presents eleven steps. The results of the carbon footprint of the UAEMéx in 2021 were 14,077,136.90 kg of CO2e, and considering that the total of the university community at that time was 105,249 members, the amount per capita was 133.75 kg of CO2e/person/year. On the other hand, for the year 2022, the carbon footprint was 28,019,621.33 kg of CO2e, and the per capita of 261.30 kg of CO2e/person/year, considering that the university community was cemented to 107,231 members. Based on the results obtained, neutralization strategies were developed, consisting of a list of activities aimed at reducing greenhouse gas emissions. Finally, the conclusions of this research are presented.